Large-molecular-weight benzoxazine resin, resin composition for copper-clad plate and preparation methods of large-molecular-weight benzoxazine resin and resin composition
By introducing bifunctional compounds into benzoxazine resins, a large molecular weight benzoxazine resin was prepared, and a resin composition for copper clad plates was formed in combination with other resins, which solved the problem of insufficient flow glue and heat resistance in the pressing process of conventional resins, and realized a resin material of high-performance copper clad plates.
Patent Information
- Application Number
- CN202411954229.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-11
AI Technical Summary
Conventional benzoxazine resin has a small molecular weight, is prone to flushing during the pressing plate, and has low heat resistance, which cannot meet the requirements of high-frequency and high-speed copper clad plates for matrix resin.
By introducing a bifunctional compound into the benzoxazine resin, increasing the molecular weight and crosslinking density of the system, a high-molecular weight benzoxazine resin was prepared, and a biphenyl epoxy resin and a phenolic resin were combined to form a resin composition for copper clad plates.
The weight average molecular weight of the high-molecular-weight benzoxazine resin exceeds 1000, which significantly reduces the problem of flowing glue, and its heat resistance is improved to Tg≥180°C. The resin composition for copper clad plates has excellent dielectric properties, flame retardancy and comprehensive properties.
Smart Images

Figure BDA0005215509370000011 
Figure BDA0005215509370000021 
Figure BDA0005215509370000022
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of benzoxazine resin modification and copper-clad laminates, and specifically relates to a high-molecular-weight benzoxazine resin, a resin composition for copper-clad laminates, and a preparation method thereof. Background Art
[0002] Copper clad laminate is an important substrate for manufacturing PCB boards. Its downstream products are oriented to communication equipment, consumer electronics, computers, automotive electronics, industrial control and medical, aerospace and other fields. It can be said that copper clad laminate is the upstream basic material for various circuit systems. With the surge in demand for various electronic consumer products, the scale of my country's copper clad laminate market has shown an upward trend year by year. Communications, IDC and automobiles are the three largest areas of board usage. Communications infrastructure, data centers in computers and automotive boards will be the three fastest growing sectors in the next five years. Among them, the growth of communication infrastructure boards is driven by the new demand opened by 5G, while data centers and automotive boards are driven by structural changes, which are ultimately reflected in the demand for ordinary copper clad laminates (FR-4, FR-1, FR-2, CEM), high-speed copper clad laminates (classified as conventional FR-4) and high-frequency copper clad laminates (mainstream includes hydrocarbon and PTFE substrates) The explosion. With the rapid development of the copper clad laminate market, higher requirements are also put forward for the commonly used matrix resins of copper clad laminates.
[0003] Benzoxazine resin is a six-membered heterocyclic compound containing C, N, and O elements synthesized from phenolic compounds, primary amine compounds, and formaldehyde. Under heating or catalytic conditions, it undergoes ring-opening polymerization to generate a network structure containing N and O similar to phenolic resin. Compared with traditional thermosetting resins such as epoxy resins and phenolic resins, it has the advantages of high glass transition temperature, low water absorption, low curing shrinkage, low dielectric constant and dielectric loss. However, conventional benzoxazine resins such as bisphenol A and bisphenol F benzoxazine resins have a small molecular weight, are prone to glue flow during the pressing process, and have low heat resistance, and are gradually unable to meet the requirements of high-frequency and high-speed copper clad laminates for base resins. Therefore, people have tried to modify the basic benzoxazine resin to improve its performance, such as Chinese invention patents CN 107522831 A, CN 113429363 A, CN101824146A, etc., which introduce silicon groups and new phenol sources into the benzoxazine molecular structure to improve the heat resistance of the resin. However, the molecular weight of the synthesized resin is relatively small, and there is still a serious technical problem of glue flow during the pressing process, which seriously limits the subsequent application of the resin in the field of copper clad laminates. Summary of the invention
[0004] The object of the present invention is to provide a high molecular weight benzoxazine resin, a resin composition for copper clad laminates and a preparation method thereof. The prepared high molecular weight benzoxazine resin has a weight average molecular weight greater than 1000, which effectively solves the problem of glue flow in the subsequent plate pressing process.
[0005] The purpose of the present invention is achieved through the following technical solutions:
[0006] A high molecular weight benzoxazine resin, the chemical structure of which is as follows:
[0007]
[0008] Wherein, n is any integer from 1 to 7;
[0009] R1 is -C(CH3)2-, -CH2-, -SO2, -C(CH3)2-, -C(CF3)2-, -O-, -CO-,
[0010]
[0011] R2 is -CH3, -CH2CH3, -CH2CH2CH3, -CH(CH3)2, -CH2CH2CH2CH3,
[0012]
[0013] To achieve the above object, the present invention also provides a method for preparing a high molecular weight benzoxazine resin, comprising the following steps:
[0014] S1. reacting phenols, paraformaldehyde and primary amine in the presence of catalyst A to produce a benzoxazine resin;
[0015] S2. further reacting the benzoxazine resin with a bifunctional compound and a catalyst B to generate a high molecular weight benzoxazine resin.
[0016] Among them, the specific preparation method of the high molecular weight benzoxazine resin is as follows:
[0017] S1. Add polyformaldehyde and primary amine compounds in a molar ratio of aldehyde group to amino group of 2 to 4:1 to a reactor A equipped with a stirrer, a thermometer, and a condenser, then add toluene 1 to 3 times the total weight of the polyformaldehyde and primary amine compounds, stir evenly, then add 1‰ to 1% of the total weight of the materials in the reactor, catalyst A, heat to 50 to 80°C and react for 0.5 to 6 hours. Then add a phenolic compound in a molar ratio of hydroxyl group to amino group of 0.8 to 1.2:1, heat to reflux temperature to react for 6 to 12 hours, let stand for 2 to 4 hours, wash with water and remove the solvent to obtain benzoxazine resin;
[0018] S2. In a reactor B equipped with a stirrer, a thermometer, and a condenser, a benzoxazine resin and a bifunctional compound are added in a molar ratio of 1:0.1-0.3, and then a solvent is added with a weight that is 1-3 times the total weight of the benzoxazine resin and the bifunctional compound, and the temperature is raised to 60-100°C for reaction for 1-4 hours, and then 1‰-1% of the total weight of the materials in the reactor is added with a catalyst B, and the temperature is raised to 100-150°C for reaction for 2-6 hours. After removing the solvent and adding 40-45% of butanone of the total weight of the product, a high molecular weight benzoxazine resin is obtained.
[0019] Wherein, the chemical structural formula of the benzoxazine resin is as follows:
[0020]
[0021] In the formula, R1 is -C(CH3)2-, -CH2-, -SO2, -C(CH3)2-, -C(CF3)2-, -O-, -CO-,
[0022]
[0023] R2 is -CH3, -CH2CH3, -CH2CH2CH3, -CH(CH3)2, -CH2CH2CH2CH3,
[0024]
[0025] Preferably, the phenols are selected from any one or more of bisphenol A, bisphenol F, bisphenol S, bisphenol B, bisphenol AF, dihydroxydiphenyl ether, dihydroxybenzophenone, bisphenol fluorene, and phenolphthalein.
[0026] Preferably, the paraformaldehyde is a mixture of one or more species with a degree of polymerization of 10-100, and the mole number thereof is calculated according to the theoretical mole number of formaldehyde, that is, mole number = mass × purity ÷ 30.
[0027] Preferably, the primary amine is selected from any one or more of methylamine, ethylamine, n-propylamine, isopropylamine, n-butylamine, tert-butylamine, cyclohexylamine, benzylamine, aniline, p-methylaniline, p-chloroaniline and p-nitroaniline.
[0028] Preferably, the catalyst A is selected from any one or more of zinc chloride, indium trihalide, ferric chloride, antimony pentachloride, trifluoromethanesulfonate, morpholine trifluoroacetate, and aluminum chloride-nitroalkyl complex.
[0029] Preferably, the difunctional compound is selected from any one or more of bisphenol A, bisphenol F, bisphenol S, bisphenol B, bisphenol AF, bisphenol fluorene, phenolphthalein, diaminodiphenylmethane, diaminodiphenyl ether, diaminodiphenyl sulfone, and hexamethylenediamine.
[0030] Preferably, the catalyst B is selected from any one or more of ferric chloride, cupric chloride, aluminum chloride, manganese chloride, zinc chloride, magnesium chloride and phosphorus pentachloride.
[0031] Preferably, the molar ratio of the benzoxazine resin to the bifunctional compound is 1:(0.1-0.3).
[0032] In addition, to achieve the above object, the present invention also provides a resin composition for copper clad laminates, comprising the following components in parts by weight:
[0033] 30 to 40 parts of the high molecular weight benzoxazine resin according to any one of claims 1 to 6, 12 to 22 parts of biphenyl epoxy resin, 11 to 21 parts of phenolic resin, 7 to 17 parts of phosphorus-containing flame retardant, 15 to 25 parts of inorganic filler, 0.05 to 0.10 parts of imidazole catalyst and 40 to 60 parts of solvent are mixed.
[0034] Preferably, the chemical structural formula of the biphenyl epoxy resin is as follows:
[0035]
[0036] In the formula, n is any integer from 1 to 10.
[0037] Preferably, in the resin composition for copper-clad laminates: the chemical structural formula of the phenolic resin is as follows:
[0038]
[0039] In the formula, m is any integer from 1 to 5.
[0040] Preferably, the phosphorus-containing flame retardant is selected from any one or more of phosphates, phosphites, phosphonates, organic phosphorus salts, phosphorus heterocyclic compounds and polymer phosphates.
[0041] Preferably, the inorganic filler is selected from any one or more of montmorillonite, calcium carbonate, magnesium hydroxide, zinc borate, talc, aluminum hydroxide, kaolin, barium sulfate, silicon dioxide, silicon powder, mica powder, hollow glass microspheres, and fumed silica.
[0042] Preferably, the imidazole catalyst is selected from any one or more of imidazole, 2-methylimidazole, 1-methylimidazole, 1,2-dimethylimidazole, 1,3-dimethylimidazole, and 2,4-dimethylimidazole.
[0043] Preferably, the solvent is selected from one or more of acetone, butanone, methyl isobutyl ketone, toluene, xylene, ethylene glycol methyl ether, ethylene glycol dimethyl ether, propylene glycol methyl ether, propylene glycol methyl ether acetate, dioxane, chloroform, and N,N-dimethylformamide.
[0044] In addition, to achieve the above-mentioned purpose, the present invention also provides a method for preparing a resin composition for copper clad laminates, comprising mixing 30 to 40 parts of a high molecular weight benzoxazine resin, 12 to 22 parts of a biphenyl epoxy resin, 11 to 21 parts of a phenolic resin, 7 to 17 parts of a phosphorus-containing flame retardant, 15 to 25 parts of an inorganic filler, 0.05 to 0.10 parts of an imidazole catalyst and 40 to 60 parts of a solvent at room temperature and stirring uniformly to obtain the resin composition for copper clad laminates.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] (1) The weight average molecular weight of conventional benzoxazine resins is 400 to 500, while the weight average molecular weight of the high molecular weight benzoxazine resin synthesized in the present invention is greater than 1000. In addition, due to the introduction of the bifunctional compound, the viscosity of the resin is further increased, which greatly reduces the problem of glue flow in the subsequent plate pressing process.
[0047] (2) The present invention introduces a bifunctional compound into the structure through molecular design, thereby increasing the system molecular weight and cross-linking density, and improving the heat resistance of the high molecular weight benzoxazine resin, with Tg≥180°C.
[0048] (3) In the resin composition for copper-clad laminates of the present invention, by introducing biphenyl epoxy resin with biphenyl structure into the formula, the biphenyl group has extremely strong rigidity, and its planar structure increases the regularity of the chain and the interaction between the groups, thereby improving the heat resistance and toughness of the system; by introducing phosphorus-containing phenolic resin, the product has a smaller molecular polarity and excellent dielectric properties. At the same time, it also has a higher phosphorus content and can act as a flame retardant.
[0049] (4) After the copper clad laminate resin composition provided by the present invention is pressed, the dielectric constant is ≤3.18; the dielectric loss is ≤0.006; the heat resistance is Td5% ≥376°C, Tg ≥189°C; and the flame retardancy is UL-V0 grade. It has the characteristics of low dielectric constant, low dielectric loss, high glass transition temperature and good flame retardancy, and has excellent comprehensive performance, and can be used as a high-performance copper clad laminate resin. DETAILED DESCRIPTION
[0050] Part I: Preparation of benzoxazine resins
[0051] In a reactor A equipped with a stirrer, a thermometer, and a condenser, add polyformaldehyde and a primary amine compound in a molar ratio of aldehyde group to amino group of 2 to 4:1, then add toluene 1 to 3 times the total weight of the polyformaldehyde and the primary amine compound, stir evenly, then add 1‰ to 1% of the total weight of the materials in the reactor, and heat to 50 to 80°C (temperature 1) for reaction for 0.5 to 6 hours (time 1). Then add a phenol compound in a molar ratio of hydroxyl group to amino group of 0.8 to 1.2:1, heat to reflux temperature (temperature 2) for reaction for 6 to 12 hours (time 2), let stand for 2 to 4 hours, wash with water, and remove the solvent to obtain a benzoxazine resin.
[0052] The amounts of raw materials used (unit: mol) and process parameters for preparing benzoxazine resins in Examples 1-1 to 1-4 are shown in Table 1.
[0053] Table 1:
[0054]
[0055]
[0056] The paraformaldehyde is a mixture of one or more compounds with a degree of polymerization of 10-100, and the mole number thereof is calculated according to the theoretical mole number of formaldehyde, that is, the mole number=mass×purity÷30.
[0057] Part II: Preparation of high molecular weight benzoxazine resins
[0058] In a reactor B equipped with a stirrer, a thermometer and a condenser, a benzoxazine resin and a bifunctional compound are added in a molar ratio of 1:0.1-0.3, and then a solvent is added with a weight of 1-3 times the total weight of the benzoxazine resin and the bifunctional compound, the temperature is raised to 60-100°C (temperature 3) and the reaction is carried out for 1-4 hours (time 3), and then 1‰-1% of the total weight of the materials in the reactor is added with a catalyst B, the temperature is raised to 100-150°C (temperature 4) and the reaction is carried out for 2-6 hours (time 4), and the solvent is removed and 40-45% of butanone of the total weight of the product is added to obtain a high molecular weight benzoxazine resin.
[0059] The raw material dosage (unit: mol) and process parameters for preparing high molecular weight benzoxazine resin in Examples 2-1 to 2-8 are shown in Table 2:
[0060] Table 2:
[0061]
[0062]
[0063] Part 3: Preparation of resin composition for copper clad laminate.
[0064] 30 to 40 parts of high molecular weight benzoxazine resin, 12 to 22 parts of biphenyl epoxy resin, 11 to 21 parts of phenolic resin, 7 to 17 parts of phosphorus-containing flame retardant, 15 to 25 parts of inorganic filler, 0.05 to 0.10 parts of imidazole catalyst and 40 to 60 parts of solvent are mixed and stirred at room temperature to obtain the resin composition for copper clad laminate.
[0065] The dosage of the raw materials in the formula of the resin composition for copper clad laminates of Examples 3-1 to 3-8 and Comparative Example 1-2 is shown in Table 3 (unit: kg).
[0066] Table 3:
[0067]
[0068] Experimental example
[0069] After applying the resin compositions for copper-clad laminates of Examples 3-1 to 3-8 and Comparative Example 1-2 to copper-clad laminates, copper-clad laminates 4-1 to 4-8 and copper-clad laminates of Comparative Example 1-2 were obtained. The performance results of the laminates are shown in Table 4.
[0070] Among them, the technical performance test methods in Table 4 are as follows:
[0071] (1) Dielectric constant
[0072] The dielectric constant at 1 GHz was measured using the flat plate method according to 2.5.5.9 of IPC-TM-650.
[0073] (2) Dielectric loss factor tangent
[0074] According to 2.5.5.9 of IPC-TM-650, use the flat plate method to measure the dielectric loss tangent at 1 GHz.
[0075] (3) Glass transition temperature (Tg)
[0076] The determination was carried out by differential scanning calorimetry according to the DSC method specified in 2.4.25 of IPC-TM-650.
[0077] (4) Thermal decomposition temperature (Td)
[0078] The test is carried out according to the method specified in 2.4.26 of IPC-TM-650.
[0079] (5) Flame retardancy
[0080] Refer to UL94 measurement standard.
[0081] (6) RC content
[0082] The RC content of the plate can be calculated by the following formula:
[0083]
[0084] Table 4:
[0085]
[0086] As can be seen from Table 4, the boards obtained by using Examples 3-1-3-8 of the present invention have excellent heat resistance, low dielectric constant and dielectric loss factor, and good flame retardancy. The board pressed by the high molecular weight benzoxazine resin of the present invention has significantly improved the degree of glue flow compared with the board pressed by the benzoxazine resin in Comparative Example 1-2, and the resin glue content is increased by about 5%. The composition of the present invention can be used in the fields of laminated boards, integrated circuit packaging, high-frequency high-speed copper-clad boards, and high-density Internet, and has broad application prospects.
Claims
1. A high molecular weight benzoxazine resin, characterized in that: The chemical structure is as follows: Wherein, n is any integer from 1 to 7; R1 is -C(CH3)2-, -CH2-, -SO2, -C(CH3)2-, -C(CF3)2-, -O-, -CO-, R2 is -CH3, -CH2CH3, -CH2CH2CH3, -CH(CH3)2, -CH2CH2CH2CH3, 2. The method for preparing a high molecular weight benzoxazine resin according to claim 1, characterized in that: The steps include: S1. reacting phenols, paraformaldehyde and primary amine in the presence of catalyst A to produce a benzoxazine resin; S2. further reacting the benzoxazine resin with a bifunctional compound and a catalyst B to generate a high molecular weight benzoxazine resin.
3. The method for preparing a high molecular weight benzoxazine resin according to claim 2, characterized in that: The chemical structural formula of the benzoxazine resin is as follows: R1 is -C(CH3)2-, -CH2-, -SO2, -C(CH3)2-, -C(CF3)2-, -O-, -CO-, R2 is -CH3, -CH2CH3, -CH2CH2CH3, -CH(CH3)2, -CH2CH2CH2CH3, 4. The method for preparing a high molecular weight benzoxazine resin according to claim 2, characterized in that: The bifunctional compound is selected from any one or more of bisphenol A, bisphenol F, bisphenol S, bisphenol B, bisphenol AF, bisphenol fluorene, phenolphthalein, diaminodiphenylmethane, diaminodiphenyl ether, diaminodiphenyl sulfone, and hexamethylenediamine.
5. The method for preparing a high molecular weight benzoxazine resin according to claim 2, characterized in that: The catalyst B is selected from any one or more of ferric chloride, cupric chloride, aluminum chloride, manganese chloride, zinc chloride, magnesium chloride and phosphorus pentachloride.
6. The method for preparing a high molecular weight benzoxazine resin according to claim 2, characterized in that: The molar ratio of the benzoxazine resin to the bifunctional compound is 1:(0.1-0.3).
7. A resin composition for copper-clad laminates, characterized in that: It includes the following components by weight: 30 to 40 parts of the high molecular weight benzoxazine resin according to any one of claims 1 to 6, 12 to 22 parts of biphenyl epoxy resin, 11 to 21 parts of phenolic resin, 7 to 17 parts of phosphorus-containing flame retardant, 15 to 25 parts of inorganic filler, 0.05 to 0.10 parts of imidazole catalyst and 40 to 60 parts of solvent are mixed.
8. A resin composition for copper-clad laminates according to claim 7, characterized in that: The chemical structural formula of the biphenyl epoxy resin is as follows: In the formula, n is any integer from 1 to 10.
9. A resin composition for copper-clad laminates according to claim 7, characterized in that: The inorganic filler is selected from any one or more of montmorillonite, calcium carbonate, magnesium hydroxide, zinc borate, talc, aluminum hydroxide, kaolin, barium sulfate, silicon dioxide, silicon powder, mica powder, hollow glass microspheres, and fumed silica.
10. The method for preparing a resin composition for copper clad laminate according to any one of claims 7 to 9, characterized in that: 30 to 40 parts of high molecular weight benzoxazine resin, 12 to 22 parts of biphenyl epoxy resin, 11 to 21 parts of phenolic resin, 7 to 17 parts of phosphorus-containing flame retardant, 15 to 25 parts of inorganic filler, 0.05 to 0.10 parts of imidazole catalyst and 40 to 60 parts of solvent are mixed and stirred at room temperature to obtain the resin composition for copper clad laminate.
Citation Information
Patent Citations
Preparation method of bisphenol A benzoxazine resin with high stability
CN101824146A
Novel high-temperature resistance low-dielectric silicon-containing benzoxazine and preparation method thereof
CN107522831A
Novel benzoxazine and synthesis method thereof
CN113429363A